POLITIK HUKUM UNDANG-UNDANG CIPTA KERJA - Yulianto, Wachid; Erofa, Andi (TERAJU: Jurnal Syariah dan Hukum, 2023)
Omnibus law or omnibus bill is the practice of drafting laws and regulations with countries that adhere to the common law tradition. In Indonesia's legal system with the civil law tradition, the preparation of laws and regulations using the omnibus method is a step that is considered to be able to overcome hyper regulation and disharmony of existing laws. With all the controversy over the formation of the UU No. 11/2020, the government emphasizes that this Law is believed to be able to revive the economy and investment from within the country and abroad. In fact, the pros and cons of drafting UU No. 11/2020 have, in fact, been submitted to the Constitutional Court for a judicial review, both in terms of formal and material trials. With the "conditional unconstitutional" decision from the Constitutional Court, it means that the government as the initiator of UU No. 11/2020 concerning Job Creation has homework to make improvements in terms of its formal formation because it is not in accordance with UU No. 12/2011 concerning the Formation of Legislation.